Synthesis of two new enrichable and MS-cleavable cross-linkers to define protein–protein interactions by mass spectrometry1. Issue 17 (7th May 2015) - Burke, Anthony M.; Kandur, Wynne; Novitsky, Eric J.; Kaake, Robyn M.; Yu, Clinton; Kao, Athit; Vellucci, Danielle; Huang, Lan; Rychnovsky, Scott D.
<x xml:space="preserve">Abstract</x> The cross-linking Mass Spectrometry (XL-MS) technique extracts structural information from protein complexes without requiring highly purified samples, crystallinity, or large amounts of material.